Mesenchymal stem cells in the fight against viruses: Face to face with the invisible enemy - Sleem, Aleen (Curr Res Transl Med, 2020)
The relative ease of isolation of mesenchymal stem cells (MSCs) from different tissues coupled with their culture expansion in vitro and their differentiation capacity to mesodermal, endodermal and ectodermal lineages have made these cells attractive for a large number of therapeutic applications. In recent years, there has been remarkable progress in the utilization of MSCs in diverse clinical indications both in animal models and human clinical trials. However, the potential of MSCs to control or treat viral diseases is still in its infancy. In this study, we report quantitative data on the MSC-based clinical trials over the last ten years as they appear on the online database of clinical research studies from US National Institutes of Health. In particular, we provide comprehensive review of either completed or ongoing clinical trials using MSCs for virus-associated diseases focusing on HIV, hepatitis B virus and COVID-19 virus.